Monetary theory as a basis for monetary policy : papers of the IEA conference held in Trento, Italy - Leijonhufvud, Axel.; International Economic Association (New York : Palgrave, 2001)
Since the inflationary 1970's, studies of monetary policy have concentrated almost exclusively on price-level stabilization and the avoidance of nominal shocks. In the aftermath of the collapse of financial bubbles in various parts of the world, the accomplishments and limitations of this dominant approach are debated in this volume edited by Axel Leijonhufvud, with contributions by a number of monetary economists, including Nobel Laureate Robert Lucas.
Papers of the conference held on Sept. 4-7, 1997 at the University of Trento.
"In association with International Economic Association."
Includes bibliographical references and indexes.
oif 01/09/15
Loan
Keywords: Monetary policy; Inflation (Finance); Money